2017
DOI: 10.1097/jom.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Perception of Risky Health Behaviors Among Construction Workers

Abstract: Objective This study aimed to evaluate construction workers’ health behaviors, attitudes, and perceptions of health risks from work related and non-work related hazards. Methods Construction workers completed a survey that assessed hazardous health behaviors (such as alcohol and tobacco use), attitudes toward health, and health risk perceptions. We compared construction workers’ health behaviors to general population data from the Behavioral Risk Factor Surveillance System. Results Construction workers rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
1
26
2
Order By: Relevance
“…16 A study done on construction workers in USA found 34.3% of their participants were smoker and that percentage was double compare to national level. 17 In India rate of smoking among construction workers was 60.2%. High percentage smoking was observed among the construction workers in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…16 A study done on construction workers in USA found 34.3% of their participants were smoker and that percentage was double compare to national level. 17 In India rate of smoking among construction workers was 60.2%. High percentage smoking was observed among the construction workers in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Health behaviour cannot be considered merely a personal choice, because educational, financial, and social circumstances have an impact on the resources and services that are available to individuals. In a study by Strickland et al (2017), the risk of engaging in unhealthy behaviours was bigger for individuals with a low education and lower worker status than for individuals with a high education and upper occupational groups. Especially those with physically burdensome jobs such as construction workers are at bigger risk.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 94%
“…Construction is one of the most dangerous industries worldwide. The health risks of construction workers depend on job tasks, each with a specific associated risk and exposure, but these workers are also passively exposed to risks produced by nearby co-workers [1][2][3]. There are many known carcinogens used in the construction industry [1].…”
Section: Introductionmentioning
confidence: 99%